The Manifestation of Mahabbah and the Social Construction of the Rolasan Tradition The Muslim Community of Tegal Regency (Analytical Study of the Social Construction of Peter L. Berger and Thomas Luckman) - Zakiyah; Ulmi Lutfiyatul Fatin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study focuses on identifying the practice of mahabbah and examining the social construction of the rolasan tradition in the Muslim community of Tegal Regency. This type of research is field research, with a qualitative research approach. Meanwhile, the scientific approach used in this study is Sufism with the concept of mahabbah Imam al Ghazali and social science with the theory of social construction Peter L. Berger and Thomas Luckman. Meanwhile, the paradigm used is constructivism. Data collection techniques were carried out through interviews, observation, and literature. Data analysis techniques used the concept of John W. Creswell. The results of the study explain, first, the manifestation of mahabbah in the rolasan tradition is connected to other spiritual practices such as gratitude, qonaah, ikhlas and others.Second, the social construction of the rolasan tradition begins with the externalization stage, which is how knowledge derived from an individual's stock of knowledge is released to understand social reality. The next process is objectification, which is a series of various traditions, both oral and symbolic, such as